The Application of Error Correction Model (ECM) in Assessing the Impact of Exchange, Interest, and Inflation Rates on the Gross Domestic Product of Indonesia - Nisa’, Milhatun (Universitas Islam Internasional Indonesia, 2022)
Economic growth is influenced by several factors, both in developing and developed countries, where the indicator of seeing high or low is seen through Gross Domestic Product (GDP). On the other hands, GDP is also influenced by other variables, in this paper the author aims to further review the relationship between GDP and interest rates, exchange rates, and inflation rates in Indonesia using a time-series technique, during the period 2010 Q1 to 2020 Q4. The data for this study were provided by Bank Indonesia and the International Monetary Fund. Since the model has a spurious problem, the error correction model was used to compare the results of the analysis in the long and short run. The cointegration estimation based on trace and max-eigen statistic is greater than the critical value which means it is cointegrated. The findings indicate that in the long run and short run, there are variables insignificantly GDP and there are changes in correlation between variables and GDP in each method that have been used, owing to this further study is needed. When to the one or two aligned macroeconomic variables applied in previous related research, this paper casts an empirical light into understanding the link. Derived from the research results, the Indonesian government should adopt appropriate policies to stabilise the monetary sector, especially the central bank which is deemed essential to improve the flexibility in adjusting and anticipating more economic issues as well as future challenges.